A Comparison Study On Sand Filter With Membrane On Kitchen Waste Water - Aiman Luddin, Nik amirull; Pauzi, Ahmad Farhan; D.Rahman, Muhammad Hazim; Suwandi, Amir Khan; Abdul kadir, Muhammad Azraie (Multidisciplinary Applied Research and Innovation, 2022)
Grey water is defined as waste water from the kitchen, toilet, anddishwashing. This grey water can be purified using filtration process so that it can beused for other purposes. In order to get optimum quality of output filtration process,the combination of filter material are essential. The aim of this study is to create akitchen waste water sand filter with a membrane. Kitchen waste water that was takenfrom residential students University Tun Hussein Onn Malaysia Pagoh campus. Silicasand, activated carbon, fiber and membrane are the material used for this filtrationsystem. For this study, a total of 7 sample of kitchen waste water are used in order toget the best result with two different types of filter. For the overall test, all the filteringsystems function well, leaving a favorable impression with the pure colour of theoutput water. The results show that Filter 1 that contains fine sand is the most suitablefilter in filtering waste water as Ph, TDS and the color of the water after the filteringshow a better result